Position-specific acceleration and deceleration profiles in elite youth and senior soccer players - Vigh-Larsen, J. F.; Dalgas, U.; Andersen, T. B. (The Journal of Strength and Conditioning Research, 2018)
The purpose of the study was to characterize and compare the position-specific activity profiles of young and senior elite soccer players with special emphasis put on accelerations and decelerations. Eight professional senior matches were tracked using the ZXY tracking system and analyzed for the number of accelerations and decelerations and running distances within different speed zones. Likewise, 4 U19 and 5 U17 matches were analyzed for comparison between youth and senior players. In senior players, the total distance (TD) was 10,776 ± 107 m with 668 ± 28 and 143 ± 10 m being high-intensity running (HIR) and sprinting, respectively. Number of accelerations and decelerations were 81 ± 2 and 84 ± 3, respectively, with central defenders performing the lowest and wide players the highest number. Declines were found between first and second halves for accelerations and decelerations (11 ± 3%), HIR (6 ± 4%), and TD (5 ± 1%), whereas sprinting distance did not differ. U19 players performed a higher number of accelerations, decelerations, and TD compared with senior players. In conclusion, differences in the number and distribution of accelerations and decelerations appeared between player positions, which is of importance when monitoring training and match loads and when prescribing specific training exercises. Furthermore, youth players performed as much high-intensity activities as senior players, indicating that this is not a discriminating physiological parameter between these players.